Managing Complex Supply Chains: Lessons from Military Logistics - Sharma, Arjun (ExcelingTech, 2023)
The prerogative of modern life is the door-step delivery of the desired products within days or a few hours of placing the order with the vendor/s. This necessitates the creation, maintenance and management of an efficient network of people and processes for production and timely delivery of the product in demand – a robust supply chain. The article is a comprehensive approach towards modern supply chain management. The purpose of this article is to illustrate the complexities faced by commercial organization in managing their supply chains, especially the ones that are spread across the globe. This article explains how the commercial world can learn from the military the ways to handle their supply chains effectively even in disruptive situations such as diseases and natural disasters in order to ensure non disruption of operations. Supply chains being lifeline of any business it pays to learn from those who are the best in managing supply chains under dire circumstances. Though blindly copying and trying to replicate supply chain management (SCM) practices adopted by the military may prove futile, a modified version to suit company-specific needs will make important differences in the efficiency of commercial operation of enterprises. We scrutinized an assortment of secondary sources including peer reviewed journal, magazines, online publications, books and newspapers to arrive at this conclusion.